Hepatoprotective potential of antioxidant potent fraction from Urtica dioica Linn. (whole plant) in CCl4 challenged rats. (2015) - Joshi, Bhuwan Chandra; Prakash, Atish; Kalia, Ajudhia N.
Abstract: The aim of the present study was to isolate hepatoprotective component from Urtica dioica Linn. (whole plant) against CCl4 -induced hepatotoxicity in-vitro (HepG2 cells) and in-vivo (rats) model. Antioxidant activity of hydro alcoholic extract and its fractions petroleum ether fraction (PEF), ethyl acetate fraction (EAF), n -butanol fraction (NBF) and aqueous fraction (AF) were determined by DPPH and NO radicals scavenging assay. Fractions were subjected to in-vitro HepG2 cell line study. Further, the most potent fraction (EAF) was subjected to in-vivo hepatoprotective potential against CCl4 challenged rats. The in-vivo hepatoprotective active fraction was chromatographed on silica column to isolate the bioactive constituent(s). Structure elucidation was done by using various spectrophotometric techniques like UV, IR, 1 H NMR, 13 C NMR and MS spectroscopy. Ethyl acetate fraction (EAF) of hydro-alcoholic extract of U. dioica possessed the potent antioxidant activity viz. DPPH (IC50 78.99 ± 0.17 μg/ml) and NO (IC50 101.39 ± 0.30 μg/ml). The in-vitro HepG2 cell line study showed that the EAF prevented the cell damage. The EAF significantly attenuated the increased liver enzymes activities in serum and oxidative parameters in tissue of CCl4 -induced rats, suggesting hepatoprotective and anti-oxidant action respectively. Column chromatography of most potent antioxidant fraction (EAF) lead to the isolation of 4-hydroxy-3-methoxy cinnamic acid (ferulic acid) which is responsible for its hepatoprotective potential. Hence, the present study suggests that EAF of hydro-alcoholic extract has significant antioxidant and hepatoprotective potential on CCl4 induced hepatotoxicity in-vitro and in-vivo .